The impact of elite endurance activity on cardiac remodelling in asians: an echocardiographic case control study. (3rd October 2022) - Tan, V; Koh, X H; Tan, F; Hazli, H; Ling, L H; Yeo, T J
Abstract: Background: Prolonged endurance training results in physiological changes to elite athletes' hearts. These changes include thickened left ventricular (LV) walls and dilated left and right ventricles that may overlap with those from pathological conditions such as hypertrophic cardiomyopathy, dilated cardiomyopathy and arrhythmogenic cardiomyopathy. While reference ranges for elite black and white athletes have been published to facilitate differentiation of physiology from pathology, data on Asian athletes remains scarce. With increasing Asian representation in international sport, it is important to ascertain the extent of physiological cardiac remodelling in Asian athletes. Purpose: This study aimed to compare echocardiographic parameters of elite endurance athletes (EAs) and non-endurance controls and describe reference ranges in this population of Asian athletes. Methods: Consecutive elite athletes engaging in endurance sport were identified from the Singapore Sports Cardiology Registry from January to October 2018. Controls were obtained from 3 sources: (a) skill-based athletes from the Singapore Sports Cardiology Registry, (b) healthy non-athletic volunteers from a national atrial fibrillation registry, and (c) healthy non-athletic volunteers from a national heart failure registry. All participants underwent resting two-dimensional, M-mode and Doppler transthoracic echocardiography and findings from EA were compared with controls. Results: 165 participants (55 EAs, 110 controls) were analysed (median age 29 years, male gender n=95; 58%, Chinese ethnicity n=55 for EAs; 100%) Baseline characteristics between both groups were comparable (Table 1). EAs had larger LV wall thickness (9.2 vs. 8.1 mm, p<0.001), LV cavity size (50.7 vs. 48.2 mm, p<0.001), LV mass index (98.4 vs. 73.8 g/m 2, p<0.001), aortic root diameter at sinus of Valsalva (30.6 vs. 28.9 mm, p<0.01), right ventricular dimensions and biatrial volumes compared to controls (Table 2). Similar results were noted after indexing to body surface area. These associations also persisted after adjusting for age. Conclusion(s): Endurance activity in elite Singaporean Chinese athletes was associated with significant structural and functional cardiac remodeling compared to controls. Reference ranges for echocardiographic parameters in this population were described, allowing for more accuracy when differentiating physiology from pathology in Asian athletes. Funding Acknowledgement: Type of funding sources: None.